The Influence of School Culture on the Performance of Senior High School Teachers - Dwi Liswantari; Maman Suryaman; Bambang Ismaya (South Sulawesi Education Development (SSED), 2025)
This study aims to analyze the influence of school culture on teacher performance at SMAIT Mentari Ilmu Karawang. A positive school culture is expected to improve teacher performance, which in turn will affect the quality of education in the school. This study uses a quantitative approach with a regressional survey method to analyze the relationship between school culture as an independent variable and teacher performance as a dependent variable. Data was collected through a questionnaire filled out by 35 teachers. The results of the analysis showed that school culture had a positive and significant effect on teacher performance, with a correlation coefficient of 0.719 and an R-Square value of 51.7%, indicating that more than half of the variation in teacher performance can be explained by school culture. However, this study also found that the dimension of teacher and student involvement in school activities still needs to be improved. The implication of this research is the importance of creating an inclusive and collaborative school culture to improve teacher performance. The suggestion for schools is to strengthen teacher and student engagement and provide greater space for participation in decision-making to improve school culture and support teacher performance improvement more effectively.